Using the CIFIST grid of CO5BOLD 3D model atmospheres to study the effects of stellar granulation on photometric colours - II. The role of convection across the H-R diagram - Kucinskas, Arunas; Klevas, Jonas; Ludwig, Hans-Günter; Bonifacio, Piercarlo; Steffen, M.; Caffau, Elisabetta (Astronomy and astrophysics, 2018)
Aims. We studied the influence of convection on the spectral energy distributions (SEDs), photometric magnitudes, and colour indices of different types of stars across the H-R diagram.Methods. The 3D hydrodynamical CO5BOLD, averaged ⟨3D⟩, and 1D hydrostatic LHD model atmospheres were used to compute SEDs of stars on the main sequence (MS), main sequence turn-off (TO), subgiant branch (SGB), and red giant branch (RGB), in each case at two different effective temperatures and two metallicities, [M∕H] = 0.0 and − 2.0. Using the obtained SEDs, we calculated photometric magnitudes and colour indices in the broad-band Johnson-Cousins UBVRI and 2MASS JHKs, and the medium-band Strömgren uvby photometric systems.Results. The 3D-1D differences in photometric magnitudes and colour indices are small in both photometric systems and typically do not exceed ± 0.03 mag. Only in the case of the coolest giants located on the upper RGB are the differences in the U and u bands able reach ≈−0.2 mag at [M∕H] = 0.0 and ≈−0.1 mag at [M∕H] = −2.0. Generally, the 3D-1D differences are largest in the blue-UV part of the spectrum and decrease towards longer wavelengths. They are also sensitive to the effective temperature and are significantly smaller in hotter stars. Metallicity also plays a role and leads to slightly larger 3D-1D differences at [M∕H] = 0.0. All these patterns are caused by a complex interplay between the radiation field, opacities, and horizontal temperature fluctuations that occur due to convective motions in stellar atmospheres. Although small, the 3D-1D differences in the magnitudes and colour indices are nevertheless comparable to or larger than typical photometric uncertainties and may therefore cause non-negligible systematic differences in the estimated effective temperatures.
Die 5 im Text ist hochgestellt
Gesehen am 18.11.2019